An Analysis of Arabic Club Extracurricular Activities on Speaking Skills at Daruttauhid Al Hasaniyyah Lampung Islamic Boarding School - Erwanto, Nanang; Izzah, Nailul; Syaifullah, Muhammad (International Journal on Advanced Science, Education, and Religion, 2025)
This study aims to describe the implementation of extracurricular activities of Arabic clubs, analyze Arabic club activities that focus on speaking skills, and identify supporting and inhibiting factors of these activities. This type of research is qualitative field research. The object of this research is the students of class Spm - 4 Muhadloroh, which totals 30 students at the Daruttauhid Al Hasaniyyah Islamic boarding school Lampung. The data analysis techniques used are data collection, data reduction, data presentation, and conclusion drawn. The data in this study were obtained through observation, interviews, and documentation. Interviews were conducted with Arabic teachers and students. The results of the observation show that the extracurricular activities of the Arabic club are carried out on the night of the week of ba'da isya, namely at 20.30 – 21.30 WIB. This extracurricular has several activities, namely muhadatsah, ilqo mufrodat, ta'lim luhgah, khitobah, Arabic MC. The supporting factors for this activity are the presence of professional educators and support from parents. Meanwhile, the inhibiting factors are, the lack of affirmation to get used to communicating using Arabic, lack of motivation, differences in individual abilities, and lack of biah lughawiyyah. This study provides practical insights for Islamic boarding school managers and Arabic language teachers in designing effective extracurricular activities to improve students' speaking skills so that it is recommended that there be periodic evaluations and variations of methods in Arabic Club to optimize the improvement of students' speaking skills